The Impact of AI-Based SMART Pancasila Learning Media on Students' Understanding of Pancasila Values (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to design, develop, and evaluate the validity, practicality, and effectiveness of an AI-powered interactive platform, SMART (Integrated Responsive Active Media System) Pancasila, specifically engineered to enhance the comprehension of national values among fifth-grade elementary students. Method: Employing a quantitative approach with a quasi-experimental pre-test–post-test control group design, the research involved 60 students from SDN Jabungan and SDN Jeketro. Data collection utilized expert validation sheets, user feedback questionnaires (from teachers and students), and cognitive assessment tests, which were subsequently analyzed using independent sample t-tests and N-Gain scores. Results: The findings indicate that SMART Pancasila is highly feasible, achieving an average expert validation score of 3.78 and exceptional practicality ratings from teachers (3.90) and students (3.75). Regarding effectiveness, a significant improvement in student understanding was observed, evidenced by a high-category N-Gain score of 0.72 and a substantial effect size (d = 1.70). Novelty: The originality of this research lies in the integration of an adaptive AI system that provides personalized learning paths, analyzes student error patterns, and delivers automated feedback within a character education framework, effectively transforming abstract Pancasila principles into concrete conceptual mastery for primary learners.